تأثير خلائط الطحالب البحرية كأوساط زراعية في إنبات بذور الغلاديشيا Gleditsia triacanthos L. وفي مؤشرات نمو بادراتها - علاء الدين حسن; شحادة غالب; الأسو إسعاف (Latakia University Journal -Biological Sciences Series, 2013)
تم في هذا البحث استخدام بقايا الطحالب البحرية المغسولة مع فرشة الغابة والتربة الزراعية والرمل منفردة أو في خلائط مختلفة في نسبها لدراسة تأثير الأوساط الزراعية في إنبات بذور الغلاديشياGleditsia triacanthos L. من العائلة الفولية Fabaceae ونمو بادراتها. وأظهرت النتائج عدم صلاحية بقايا الطحالب البحرية غير المغسولة كوسط نقي لإنبات البذور, بينما أدت إضافة الطحالب المغسولة إلى الأتربة المعدنية (رمل, تربة) إلى تحسين القدرة الإنباتية (%) ومؤشرات النمو الطولية والكمية والوزنية في الغلاديشياGleditsia triacanthosL.. وكشفت عن إمكانية استخدام هذه البقايا الغنية بالمادة العضوية والأملاح المعدنية والتي تلقيها أمواج البحر على الشاطئ كأحد مكونات الوسط الزراعي الذي يمتاز بوفرته محلياً وباستثمارات ضئيلة وغير مكلف من الناحية الاقتصادية وبالتالي تقليل التكاليف الباهظة الناجمة عن استخدام الأوساط الزراعية المستوردة مثل البيتموس أو غيره. وفي الوقت نفسه تعتبر حلاً اقتصادياً وفعالاً لإدارة المخلفات النباتية البحرية والتخلص من مشكلة التلوث بهذه المخلفات وتحسين مظهر الشواطئ والمنتزهات البحرية من الناحية الجمالية. In this research residues of washed marine seaweed were used with forest floor, agricultural soil and sand (pure or mixtures of different ratios), to study the effect of substrates on seed germination and seedlings growth of Gleditsia triacanthos L. from the family Fabaceae. The results showed the disqualification of unwashed marine seaweed residues as a pure growth medium for seed germination. Nevertheless, the addition of washed seaweed into mineral dust (sand, soil) improved the germination capacity (%) and growth indicators (length, weight, and quantity) in Gleditsia triacanthos L. It also revealed the possibility of using these residues, which are rich in organic matter and mineral salts brought to the beach by the tide, as a locally available component for the substrate. Economically speaking, this will be an inexpensive alternative and will reduce the costs caused by using imported substrates such as peat moss. At the same time, this will be an economic and effective solution for the management and disposal of marine plant waste and pollution problem caused by these residues. Consequently, it will lead to the aesthetic improvement of beaches and marine parks.